Liturgical categories and ritual process. The Nordic welfare states encounter with workplace health problems - Hans-Einar Hem (AM. Rivista della Società Italiana di Antropologia Medica, 2001)
Liturgical categories and ritual process.The Nordic welfare states encounter with workplace health problems